Air pollution after acute bronchiolitis is a risk factor for preschool asthma: a nested case-control study - Hao-Wei Chung; Hui-Min Hsieh; Chung-Hsiang Lee; Yi-Ching Lin; Yu-Hsiang Tsao; Ming-Chu Feng; Chih-Hsing Hung (BMC, 2023)
Abstract Background Acute bronchiolitis and air pollution are both risk factor of pediatric asthma. This study aimed to assess subsequent exposure to air pollutants related to the inception of preschool asthma in infants with acute bronchiolitis. This study aimed to assess subsequent exposure to air pollutants related to the inception of preschool asthma in infants with acute bronchiolitis. Methods A nested case-control retrospective study was performed at the Kaohsiung Medical University Hospital systems between 2009 and 2019. The average concentration of PM10, PM2.5, SO2, NO, NO2, and NOX was collected for three, six, and twelve months after the first infected episode. Adjusted regression models were employed to evaluate the association between asthma and air pollution exposure after bronchiolitis. Results Two thousand six hundred thirty-seven children with acute bronchiolitis were included. Exposure to PM10, PM2.5, SO2, NO, NO2, and NOX in the three, six, and twelve months following an episode of bronchiolitis was found to significantly increase the risk of preschool asthma in infants with a history of bronchiolitis.(OR, 95%CI: PM10 = 1.517-1.559, 1.354-1.744; PM2.5 = 2.510-2.603, 2.148-3.061; SO2 = 1.970-2.040, 1.724-2.342; ; NO = 1.915-1.950, 1.647-2.272; NO2 = 1.915-1.950, 1.647-2.272; NOX = 1.752-1.970, 1.508-2.252) In a sensitive analysis of hospitalized infants, only PM10, PM2.5, SO2, and NO were found to have significant effects during all time periods. (OR, 95%CI: PM10 = 1.613-1.650, 1.240-2.140; PM2.5 = 2.208-2.286, 1.568-3.061; SO2 = 1.679-1.622, 1.197-2.292; NO = 1.525-1.557, 1.094-2.181) Conclusion The presence of ambient PM10, PM2.5, SO2 and NO in the three, six, and twelve months following an episode of acute bronchiolitis has been linked to the development of preschool asthma in infants with a history of acute bronchiolitis.